Aging in Ghana: Setting Priorities for Research, Intervention and Policy - de-Graft Aikins, A.; Apt, N. (My University, 2016)
Ghana’s aging population has increased seven-fold over a fifty year period—from 213,477 in 1960 to 1,643,381 in 2010 (Ghana Statistical Service (GSS), 2013). The current proportion of Ghanaians over 60 years is 5%; this is one of the highest proportions of that age category in sub-Saharan Africa (GSS, 2013). Over the next few decades, population aging in Ghana is likely to increase, like other African countries, at a rate that exceeds that of high income countries of Europe and North America (Ayernor, 2012; de-Graft Aikins et al, 2016; Minicuci et al., 2014). The socio-economic and socio-cultural challenges associated with aging in Ghana require interventions and policies that address the multifaceted needs of older Ghanaians. These services and policies, as regional and global experts observe (cf. Apt, 1996; Makoni and Stroeken, 2002; UN, 2013) have to be context-specific and based on evidence informed by robust multidisciplinary programmes of research that examine aging issues from micro (e.g. illness experience) to macro (e.g. social security) levels. There has been six decades of research on aging in Ghana. However there has been no attempt to synthesise the available body of work to address current and future research, practice and policy challenges. The aim of this special section of Ghana Studies, titled Aging in Ghana: Addressing the Multifaceted Needs of Older Ghanaians, is to address this major gap. This volume is the product of a symposium organized by the Centre for Social Policy Studies (CSPS), University of Ghana, in December 2014 that brought together researchers working on different aspects of aging from anthropology, psychology, public health, social policy studies and sociology. This issue consists of papers originally presented at the symposium and new papers submitted in response to a call for submissions to the issue. In this [End Page 35] editorial we present a brief history of aging research in Africa to place aging in Ghana within the regional context. We then introduce the special issue papers and outline emerging insights for strengthening aging research, intervention and policy in Ghana.
Keywords: Ghana; research; policy; Ageing